Kombinasi Strategis Kepemimpinan Transformasional, Komunikasi Internal, Kerjasama Tim, dan Motivasi Ekstrinsik dalam Peningkatan Kinerja Karyawan - Hidayat, Muhammad Taufik; Fitriasuri, Fitriasuri; Septayudha, Irwan; Agustian, Wiwin (Jurnal Ilmiah Global Education, 2025)
This study aims to analyze the influence of transformational leadership style, internal communication, teamwork, and extrinsic motivation on employee performance at PT. Agro Gemilang Surya. The background of this research is the low achievement of productivity targets caused by the suboptimal application of transformational leadership, weak communication, low team synergy, and insufficient extrinsic motivation. This research employs a quantitative method with a saturated sample of 51 employees. Data were collected through questionnaires and analyzed using SPSS version 22 through instrument tests, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination (R²). The research findings indicate that these four variables, both partially and simultaneously, have a positive and significant effect on employee performance. These results highlight the importance of enhancing transformational leadership, improving internal communication, strengthening teamwork, and providing optimal extrinsic motivation to support improvements in employee performance and the achievement of company targets.